2014
DOI: 10.1097/grf.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Stress Reduction

Abstract: Chronic stress contributes to preterm birth (PTB), through direct physiological mechanisms or behavioral pathways. This review identified interventions to prevent PTB through decreased maternal stress. Studies were grouped according to intervention: group prenatal care (11 studies), care coordination (8 studies), health insurance expansion (4 studies), expanded prenatal education/support in the clinic (8 studies), home visitation (9 studies), telephone contact (2 studies), or stress-reduction strategies (5 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Centering reduces distress, improves lifestyle, and bolsters social support in high-risk women (Heberlein et al 2016; Ickovics et al 2011). Any of these changes might ameliorate immune activation in the placenta (Straub et al 2014) and their role should be explored in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Centering reduces distress, improves lifestyle, and bolsters social support in high-risk women (Heberlein et al 2016; Ickovics et al 2011). Any of these changes might ameliorate immune activation in the placenta (Straub et al 2014) and their role should be explored in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results extend current knowledge of the adverse effects of stress during pregnancy and provide further support for the value of efforts to find effective methods to reduce stress during pregnancy. A recent review of stress reduction strategies during pregnancy [61] reported that group prenatal care programs, such as Centering Pregnancy [62], provided education and emotional support throughout pregnancy and were the most effective interventions for decreasing preterm birth and low birth weight. We suggest that health care providers make an effort to discuss stress during pregnancy with their patients, and to provide advice for stress relief interventions as a way to potentially improve pregnancy experience, neonatal health, and to limit unnecessary health care expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for PTB include, but are not limited to, multiple pregnancy, a previous PTB, or short birth interval (less than 6 months) . Specific psychosocial risk factors include stress, anxiety, depression, as well as smoking, drug use, low socio‐economic status, and ethnicity …”
mentioning
confidence: 99%
“…Stress, in the form of stressful life events, catastrophic events, or chronic stress, has been linked to PTB or shortened gestational age . The biological mechanisms linking anxiety or depression to PTB are not fully understood; however, growing evidence suggests that allostatic load, or the cumulative effects of chronic stressors, may impact PTB through inflammatory, neuroendocrine, and immune pathways . In addition, stress and anxiety are associated with increased risk‐taking behaviours (such as smoking and substance abuse), thereby increasing a woman's risk for PTB …”
mentioning
confidence: 99%